Феномен корупції в системі публічного управління: теоретичні аспекти наукового дискурсу - Мартинов, Д. Ю.; Обушна, Н. І. (ДКС Центр, 2020)
У статті обґрунтовано актуальність дослідження феномену корупції в системі публічного управління та необхідність теоретичного формування підґрунтя національної антикорупційної політики як пріоритетного напряму спеціальності “Публічне управління та адміністрування”. У контексті цивілізаційно-історичного контенту підтверджено, що корупційні практики супроводжують практично всю історію людського буття. Проаналізовано етимологічне походження поняття “корупція” та її соціально-правову природу. Окреслено сучасні теоретичні підходи до трактування сутності поняття “корупція” та досліджено феномен корупції в системі публічного управління. На цій підставі констатовано, що корупційні прояви становлять реальну загрозу існуванню конституційно заявлених параметрів української держави (демократичних, соціальних, правових), створюючи тим самим міцне підґрунтя для процвітання в країні системної корупції, агресивно-руйнівний потенціал якої проявляється в її інституціональній експансії. The article substantiates the relevance of the study of the phenomenon of corruption in the public administration system and the need for theoretical formation of the basis of national anticorruption policy as a priority area of the specialty “Public Administration”. In the context of civilization-historical content, it has been confirmed that corrupt practices accompany almost the entire history of human existence. The etymological origin of the concept of “corruption”, its sociolegal nature and dimensions (social, political-economic, criminological, criminal-legal) are analyzed. Modern theoretical approaches to the interpretation of the essence of the concept of “corruption” are outlined and the phenomenon of corruption in the system of public administration is studied. On this basis, it is stated that corruption is a real threat to the constitutionally declared parameters of the Ukrainian state (democratic, social, legal), thus creating a solid foundation for the prosperity of systemic corruption, aggressive and destructive potential of which is manifested in its institutional expansion. Emphasis is placed on the need to take into account the socio-cultural nature of corruption, which will provide an adequate description of the role of this complex multi-level institution. It is the transformational model of the “society-man” connection that allows us to consider and measure the perception of corruption in public authorities by ordinary Ukrainians, to combine its objective and subjective dimensions, to find the right transition from one level of description to another. It is concluded that corruption is an antisocial, immoral and illegal phenomenon, which will ultimately lead the state not only to the contempt of other states, to significant damage to the economy, but also to the degradation and decline of the state as a whole. Therefore, in order to overcome crisis-type corruption, it is necessary to carry out deep social reforms, through consistent systemic and coordinated actions, united by one concept, which will change the way of life and ensure the formation of a legal social worldview.
Феномен коррупции в системе публичного управления: теоретические аспекты научного дискурса
Keywords: корупція; корупційне правопорушення; публічне управління; антикорупційна політика; органи публічної влади; corruption; corruption offense; public administration; anti-corruption policy; public authorities